Analysis of miRNA expression profiles in the liver of ClockΔ19 mutant mice - Wang, Yanli; Lv, Ke; Zhao, Mei; Chen, Hailong; Ji, Guohua; Zhang, Yongliang; Wang, Tingmei; Cao, Hongqing; Li, Yinghui; Qu, Lina (PeerJ, 2019)
The circadian clock controls the physiological functions of many tissues including the liver via an autoregulatory transcriptional−translational feedback loop, of which CLOCK is a core positive component. In addition, many studies have indicated that microRNAs (miRNAs) regulate liver function. However, how CLOCK-regulated miRNAs are linked to liver function remains largely unknown. In this study, miRNAs expression profiles were performed in the liver of ClockΔ19 mutant mice. Compared to wild type mice, totals of 61 and 57 putative CLOCK-regulated miRNAs were differentially expressed (fold change absolute value ≥2) at zeitgeber time 2 and zeitgeber time 14, respectively. According to the pathway analyses, the target genes of differentially expressed miRNAs were mainly involved in pathways in cancer, the PI3K-Akt signaling pathway and the MAPK signaling pathway. Protein−protein interaction analyses revealed that the hub genes were primarily associated with pathway in cancer and circadian rhythms. Expression validation showed that while the expression levels of miR-195 and miR-340 were up-regulated, the rhythms of these two miRNAs were always maintained. The expression level of nr1d2 mRNA was down-regulated. We identified a number of prospective CLOCK-regulated miRNAs that play roles in the various physiological processes of the liver, providing a reference to better understanding the potential regulatory mechanisms in the liver.
Keywords: Liver; Clock mutation; Circadian rhythms; miRNAs